Influence of Cultivar on Nutritional Composition and Nutraceutical Potential of Pecan Growing in Uruguay - Ferrari, Virginia; Gil, Guillermo; Heinzen, Horacio; Zoppolo, Roberto; Ibáñez, Facundo (Frontiers in Nutrition, 2022)
Composition and antioxidant properties of sixteen pecan [Carya illinoinensis (Wangenh) K. Koch] cultivars grown simultaneously in a single experimental orchard in Uruguay were evaluated to characterize their nutritional properties and nutraceutical potential. The percentage of oil, moisture, ash, minerals, and protein were determined as well as fatty acid profile. Total phenolic compounds (18-41 mg Gallic Acid Equivalents (GAE) /g), condensed tannin (2-12 mg Catechin Equivalents (CE)/g) and tocopherols (110-163 µg/g) contents were estimated in nut kernels. Total phenolic compounds (32-117 mg GAE/g), condensed tannins (130-357 mg CE/g) and total anthocyanins (1-3 mg 3-glucoside cyanidin/g) were also determined for pecan shells. The antioxidant activity in shells (57.15-578.88 µmol Trolox Equivalents (TE)/g) was 5 times higher compared to kernels (23.15-156.60 µmol TE/g) measured with hydrophilic ORAC. Bioactive compounds concentrations present statistically significant genetic variability between cultivars studied (p < 0.05). The presence of phenolic compounds was related with high antioxidant capacity in kernels and shells, and a strong correlation between content of total phenolic compounds and condensed tannins in pecan shells was found. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) show association between cultivars and the observed variables. The nutritional profile in the different cultivars showed the trends described in other countries, but this work shows some significant differences that could be attributed to the specific edaphoclimatic conditions of cultivation in Uruguay.